1984
DOI: 10.1083/jcb.99.6.2309
|View full text |Cite
|
Sign up to set email alerts
|

Differential proliferative responses of cultured Schwann cells to axolemma- and myelin-enriched fractions. I. Biochemical studies.

Abstract: Cultured rat Schwann ceils were treated for 72 h with axolemma-and myelinenriched fractions prepared from rat brainstem.[3H]Thymidine was added to the cultures 48 h before the termination of the experiment. Although, both fractions produced a dosedependent uptake of label into Schwann cells, the shape of the dose response curves and rates at which [3H]thymidine was incorporated were different. The axolemma-enriched fraction produced a sigmoid dose response curve with a Hill coefficient of 2.05. The dose respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
67
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 19 publications
9
67
0
Order By: Relevance
“…The initial increase of total RNA and 0-actin mRNA levels per milligram wet weight of nerves for the first 4 days after injury was identical between crushed nerves and transected nerves, which could be attributed to the initial Schwann cell proliferation (Bradley and Asbury, 1970;Clemence et al, 1989) caused by myelin disintegration and macrophage invasion into the endoneurial space, both of which are commonly seen in crushed and transected nerves and are a source of potent mitogens for Schwann cells (Yoshino et al, 1984;Baichwal et al, 1988). The following phase of increased total RNA and P-actin mRNA levels per unit tissue weight observed in crushed nerves, which was lacking in the transected nerves, may be caused by Schwann cell proliferation due to contact with regenerating neurites from the crushed stumps (Salzer and Bunge, 1980;De Vries et al,, 1982;Sobue and Pleasure, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The initial increase of total RNA and 0-actin mRNA levels per milligram wet weight of nerves for the first 4 days after injury was identical between crushed nerves and transected nerves, which could be attributed to the initial Schwann cell proliferation (Bradley and Asbury, 1970;Clemence et al, 1989) caused by myelin disintegration and macrophage invasion into the endoneurial space, both of which are commonly seen in crushed and transected nerves and are a source of potent mitogens for Schwann cells (Yoshino et al, 1984;Baichwal et al, 1988). The following phase of increased total RNA and P-actin mRNA levels per unit tissue weight observed in crushed nerves, which was lacking in the transected nerves, may be caused by Schwann cell proliferation due to contact with regenerating neurites from the crushed stumps (Salzer and Bunge, 1980;De Vries et al,, 1982;Sobue and Pleasure, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Internalization of the intact axolemmal fragments by Schwann cells does not appear to be necessary for the communication of the mitogenic signal across the Schwann cell plasma membrane [Yoshino et al, 1984;Sobue and Pleasure, 1985a]. Recent studies suggest, however, that an axolemmal hepa ran sulfate proteoglycan, itself not necessary for neuronal-Schwann cell adhesion, is necessary for the induction of Schwann cell proliferation [Rainer et al, 1985], and it seems possible that this axolemmal compo nent is in some way responsible for communi cation of the mitotic signal to the Schwann cell.…”
Section: Axoleinmal Contactmentioning
confidence: 99%
“…Much evidence has shown that the digestive process of myelin is intimately related to Schwann cell proliferation (1,2,5,8,11,20,21). The removal of the myelin sheath elicited proliferative response of Schwann cells (5,12,16).…”
mentioning
confidence: 99%